Psychometric properties of the Revised Dental Beliefs Survey - Coolidge T, Heima M, Coldwell SE, Weinstein P, Milgrom P. (Blackwell Synergy, 2005)
The objectives of this pair of studies were to examine the internal reliability, test–retest reliability, and construct validity of the Revised Dental Beliefs Survey.